The Influence of Service Quality of Terminal Inspection Service (TIS) Officers on Passenger Satisfaction at Halim Perdanakusuma International Airport, Jakarta - Istiyani, Yuniar; Fadhillah, Muhammad Zaki (CV. Rayyan Dwi Bharata, 2024)
The public's need for transportation services is increasing, and air transportation has become an option because it is more effective and efficient. This must be supported by the quality of service, security and comfort of airport facilities which support air transportation service activities. The Terminal Inspection Service (TIS) unit has the task of checking and ensuring the suitability of existing facilities at the airport terminal. This research aims to determine the influence of the service quality of TIS officers on passenger satisfaction and how much influence the service quality of TIS officers has on passenger satisfaction at Halim Perdanakusuma International Airport, Jakarta. The research method used in this research is descriptive research with a quantitative approach. The population in this study were passengers on the HLP-JOG flight route at Halim Perdanakusuma International Airport, Jakarta, with a sample size of 100 respondents. The research data collection technique uses a Likert scale questionnaire with data analysis techniques using the Simple Linear Regression Analysis Test, T Test and R square Determination Test. The results of the research show that there is an influence on the service quality of Terminal Inspection Service (TIS) officers on passenger satisfaction at Halim Perdanakusuma International Airport, Jakarta. Based on the significance value from the Coefficients table, it is 0.01 0.05 and the Adjusted R Square value or coefficient of determination is 0.742. This shows that there is a significant influence of the Service Quality of Terminal Inspection Service (TIS) officers on Passenger Satisfaction of 74.2% so there is a high correlation and the remaining 25.8% is influenced by other variables that are not included in this research.